(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This work describes the development of a fashion collection based on a survey carried out with visually impaired women. Its main problem is to understand what are the difficulties that blind people encounter in understanding works of art. This question is justified based on data from the IBGE (2010) which shows that 6.5 million Brazilians have severe visual impairment and the fashion area is not very concerned with this public. The main objective of this study, therefore, is to identify and analyze the perceptions of visually impaired people about some of Vincent Van Gogh’s paintings and, based on the methodology of in-depth interviews with two blind women, create an inclusive fashion collection based on the method project proposed by Munari (1981), Treptow (2013) and Brogin (2019). The research showed that sensory experiences, through textures, awaken sensations and experiences through touch and help visually impaired people memorize, resulting in the simplification of their routine.